Pengaruh Pendidikan Kesehatan Dengan Metode SimulasiTerhadap Pengetahuan Dan Sikap Tentang PertolonganPertama Pada Kecelakaan Di Smk Negeri 1 Mojosongo Boyolali - Saputro, Wisnu Wijiyanto; , Arief W. Jadmiko, S.Kep., Ns., M.Kep (2017)
The phenomenon of traffic accidents until now has not received public attention as the cause of death is quite large. UNICEF in 2012 reported that adolescentsaged 10 to 19 years amounted to 1.2 billion of the world where that each year anaverage of 1.4 million young people have an accident on the street. First aid theefforts to deal with the ccident victims as soon as possible at the scene.Ketrampilkan nowledge and implementation of first aid is very important ownedby teenagers, so that teens can carry out first aid measures that can reduce therisk of disability and death. One step increase knowledge and attitudes about aid is to provide health education. This study aims to determine the effect ofhealth education with simulation method on nowledge and attitudes about firstaid students of SMK Negeri 1 ojosongo Boyolali. This research is a form of reexperimental withpreandposttestwithoutcontrol.Thestudypopulationwasall classXI student at SMK Negeri 1 Mojosongo Boyolali totaled 576 students. Theresearch sample as many as 43 students with proportional random samplingtechnique. The collection of research data using a questionnaire and analyzedusing t-test. The results showed test results paired sample t-test¬ knowledge andattitudes before and after health promotion concluded there are significant healtheducation using simulation methods on knowledge and attitudes about first aidwhere health education using simulation methods effectively improve theknowledge and attitudes of help the first on the accident to students in SMKNegeri 1 Mojosongo Boyolali.Keywords: knowledge, attitude, first aid, health education, simulation methods